Gender Inequality and Caste: Field Experimental Evidence from India - Asad Islam; Debayan Pakrashi; Soubhagya Sahoo; Liang Choon Wang; Yves Zenou (Institute of Labor Economics (IZA), 2021)
Using a field experiment in India where patients are randomly assigned to rank among a set of physicians of the same gender but with different castes and years of experience, we show that the differences in patients' physician choices are consistent with gender-based statistical discrimination. Labor market experience cannot easily overcome the discrimination that female doctors suffer. Further, we find that gender discrimination is greater for lower caste doctors, who typically suffer from caste discrimination. Given the increasing share of professionals from a lower caste background, our results suggest that the 'intersectionality' between gender and caste leads to increased gender inequality among professionals in India.
Keywords: J16; J15; I15; O12; 330; caste discrimination; statistical discrimination; gender discrimination; intersectionality; affirmative action